2020
DOI: 10.1186/s12301-020-00087-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pre-operative urine culture with intra-operative stone culture: a prospective observational study

Abstract: Background It is well known that urinary calculi are associated with urinary tract infections. Post-operative sepsis is one of the major complications after various endourological procedures for stone surgeries. These episodes of sepsis occur even in negative urine cultures. Stones have been found to harbour bacteria which on fragmentation causes bacteremia and sepsis. Thus, usual practice of pre-operative urine culture cannot truly predict the occurrence of post-operative sepsis. It also seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In recent years, multiple studies arise to assess the value of calculi culture, most studies promote the usage of calculi culture as a routine examination (Songra et al, 2015;Eswara et al, 2013;Gupta et al, 2020;Ashra Mahabadi & Kumar, 2022). We highly considered the clinical importance of calculi culture in patients with negative preoperative urine culture, as the result enabled the clinician to manage patients with precision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, multiple studies arise to assess the value of calculi culture, most studies promote the usage of calculi culture as a routine examination (Songra et al, 2015;Eswara et al, 2013;Gupta et al, 2020;Ashra Mahabadi & Kumar, 2022). We highly considered the clinical importance of calculi culture in patients with negative preoperative urine culture, as the result enabled the clinician to manage patients with precision.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative calculi culture is not routinely performed in stone surgery cases, previous studies revealed the diverse result. Five studies encourage routine calculi culture examination (Songra et al, 2015;Martov et al, 2014;Gupta et al, 2020;Ashra Mahabani & Kumar, 2022), but two studies suggest the opposite (Osman et al, 2016;Elshal et al, 2014). Songra et al (2015), and Gupta et al (2020) showed the relevancy of calculi culture in urological procedures, but the included cases were all preoperative urine culture status, positive and negative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial ecology of the stone could thus be employed as a predictor of post-operative indicators of urosepsis. Stone culture is not common in endourologic surgeries, and pre-operative urine cultures have been relied on to treat post-operative infections and sepsis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Pemeriksaan ini merupakan salah satu pemeriksaan rutin sebelum dilakukannya operasi pada pasien untuk mengetahui apakah terdapat bakteri pada urine pasien, jenis bakteri dan resistensinya terhadap antibiotik. 5,[8][9][10] Teori pembentukan batu saluran kemih yang paling banyak dipakai adalah teori supersaturasi. Supersaturasi dapat terjadi jika substansi yang penyusun batu terdapat dalam jumah yang besar dalam urin.…”
unclassified